2019
DOI: 10.5114/pm.2019.93119
|View full text |Cite
|
Sign up to set email alerts
|

Body image in perimenopausal women

Abstract: Introduction: Menopause is the last natural menstruation, followed by a period of 12 months during which no bleeding occurs (WHO). This natural process results from the phasing out of the physiological activity of the ovaries and involves numerous psychological and somatic disturbances. Although perimenopausal ailments are experienced by most women, the correlation between their perception of the bodies and biopsychosocial functioning in the climacteric period is not fully understood. The aim of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…As presented in Table 1, the age range required for inclusion was generally between 40 and 65 years. 2,64,69,85,89,90,93,97,99 Other studies established the minimum age at 25, 76 30, 84 or 35 years, 5,65 and the maximum age at as high as 71 years. 84 Notably, only some of these studies reported controlling their analyses for the effect of age.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…As presented in Table 1, the age range required for inclusion was generally between 40 and 65 years. 2,64,69,85,89,90,93,97,99 Other studies established the minimum age at 25, 76 30, 84 or 35 years, 5,65 and the maximum age at as high as 71 years. 84 Notably, only some of these studies reported controlling their analyses for the effect of age.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In addition, the study by Drobnjak et al 73 categorized their participants as either pre-or postmenopausal, but the criteria used to define stages implied that perimenopausal women who experienced an irregular cycle over the past 12 months were included in the premenopausal group. All studies used self-reported menstruation history to assign menopausal stage, with the exception of the study by Szymona-Pałkowska et al 76 which assessed menopausal status by clinical interview and confirmed it with FSH and E2 levels, and the study by Gümüşsoy et al 82 in which perimenopausal women had their menopausal status diagnosed by a doctor. Notably, Baker et al 64 and Włodarczyk and Dolińska-Zygmunt 89 were the only studies that reported using the Staging of Reproductive Aging Workshop (STRAW + 10) classification, 45 considered as a gold standard to define menopausal status.…”
Section: Controlled Formentioning
confidence: 99%
See 1 more Smart Citation
“…Body image is closely related to personality and the way individuals perceive themselves greatly impacts their psychological aspects [39]. Changes in appearance and function experienced by some postmenopausal women, such as changes in body weight and shape, sleep disturbances due to night sweats, and signs of aging such as changes in skin, hair, and sexual function, may affect the way women perceive their bodies [40].…”
Section: F Body Imagementioning
confidence: 99%
“…Body image is a multidimensional concept that includes personal perceptions, attitudes, and affects the size, shape, and form of the body 1 . Women's body image‐related perception can be affected by life periods such as adolescence, pregnancy, postpregnancy, premenopause, and menopause 2–6 . Pregnancy is a period that affects maternal and infantile health; physiological and psychological changes occur in a short time during this period 7 .…”
Section: Introductionmentioning
confidence: 99%